Flow behaviour of labeled red blood cells in microchannels : a confocal micro-PTV assessment - Lima, Rui A. (2010)
The development of optical experimental techniques has contributed to obtain explanations on the blood flow behaviour through microvessels. Although the past results have been valuable, detailed studies on the flow properties of blood in the microcirculation have been limited by several technical factors such as poor spatial resolution and difficulty to obtain quantitative detailed measurements at such small scales. In recent years, due to advances in computers, optics, and digital image processing techniques, it has become possible to combine particle tracking methods with confocal microscopes. As a result, this combination has greatly increased the resolution of the conventional PIV systems and consequently provided additional detailed description on the blood cells motion not obtainable by traditional methods. In this work, we will show an overview of the most recent results on the blood flow behaviour in microchannels obtained by state-of-the-art confocal micro-PIV/PTV system.